Peningkatan dan Pengembangan Mutu Pelayanan Perpustakaan dengan Metode Quality Function Deployment (QFD) - Christin Christin; Leli Deswindi (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Increased competition in the educational institutions in attracting prospective students demanding the education providers to evaluate and improve. Various advantages offered by such excellence of lecturer and guarantee jobs for graduates and facilities, supporting infrastructure owned. In this study, researchers took the object of a university in Jakarta to translate the desire of consumers to one of the supporting facilities of the library as a medium of information through the availability of textbooks, student and faculty research and reading reference materials. With the method of Quality Function Development (QFD) obtained the final results of this study of 10 major things that are important to consumers and has the best service performance as well as 10 high priorities to library development in accordance with the wishes of consumers.Keywords: Quality Function Deployment, House of Quality, Service Quality